Condition of Hard Tissues of the Primary Teeth in Children with the Pathology of the Musculoskeletal System - Smolyar N.; Bodnaruk N. (Львівський клінічний вісник)
Introduction. In the structure of diseases of graduates of preschool institutions, 37.2% occupy the illnesses of the musculoskeletal system. The obstetrician has detected more violations of the musculoskeletal system than in school-age children, but with higher percentage of underlying structural deformations. In view of this, the period of pre-school childhood is important for the formation and preservation of health. With age in bone tissue children accumulate minerals, forming “Reserve bone bank” for the future and maintaining the optimal mineral density of bone tissue (BMD) are important. The main factors in achieving the optimal bone marrow peak in childhood are the adequate level of calcium intake, its high bioavailability, adequate amount of vitamin D in the daily ration, physical activity, sexual development and peculiarities of the physical development of the child. Aim. To study and analyze the caries of temporary teeth in children with musculoskeletal system diseases. Materials and methods. In order to study and analyze this issue 357 children aged 3-6 years who were attending the specialized groups for the children with disorders of the musculoskeletal system in kindergardens were examined. The prevalence (in %), intensity (df) of caries and the degree of the caries process activity according to N. Bidenko (2005) were estimated in all of the children. Results. The following diseases of the musculoskeletal system were detected in the examined children: in 118 (33.05%) – flatulence, in110 (30.81%) – posture disturbances, in 129 (36.14%) – combined musculoskeletal diseases including chest deformity and X- or O-shaped deformation of the lower extremities.The prevalence of caries of primary teeth in children with pathology of musculoskeletal system was 87.40 ± 1.76 % with the intensity of df = 6.12 ± 0.16 of a tooth. In girls caries prevalence was much lower – 82.18 ± 2.90 % with the intensity of df = 5.95 ± 0.22 of a tooth compared with boys – 92.35 ± 1.96 % with the df = 6.30 ± 0.23 of a tooth respectively; (р1 < 0.01, р2 < 0.05). In children with combined pathologies the prevalence of caries of primary teeth is the highest and is 94.57 ± 1.10 % with intensity of caries process df = 6.47 ± 0.35 of a tooth. Conclusions. Among the children with combined pathologies of the musculoskeletal system the states of subcompensated and decompensated stages of the caries process activity (42.63 ± 4.35 % and 43.41 ± 4.36 % respectively) are significantly more common compared with the children with specific pathologies of the musculoskeletal system.